SISI ABU-ABU KAUSALITAS DAN EVALUASINYA DALAM PEMBELAJARAN SEJARAH - Mohamad Zaenal Arifin Anis; Sriwati Sriwati; Fitri Mardiani (JURNAL SOCIUS, 2020)
The development of historical science in exploring the causes of historical phenomena or causality with monocausal and multicausal approaches has progressed rapidly. However, it is inversely proportional to the study of history which still often explains historical causality with a single one (monocausality) or a centric logo without a scientific approach with a cognitive assessment only. Whereas the causes of history can be explained by the approach of a science (monocausality) and various (multi causality) with a multidimensional approach. The purpose of this study is to provide an alternative for teachers who teach history so that students can analyze various historical causality so that they are not only able to think critically but also be creative and adults so they can get used to the differences. Likewise, the assessment must be directed towards authentic assessment that can bring students to be creative and mature so that they are familiar with differences. The source of this study is through literature studies. The results of the writing are an alternative for history teachers so that students are accustomed to analyzing causality in seeing historical phenomena both mono under the demands of the 2013 curriculum.